A Proverb is the Most Ancient Wisdom of the People - Nematovna Ochilovа Nasiba; Suranbaevna, Toychieva Nasibakhon; Gaibullaevna, Temirova Shoira (European Journal of Life Safety and Stability (2660-9630), 2021)
This article is devoted to the description of paremias as an exponent of folk wisdom. Proverbs and sayings are special units of the language, interesting as a means of understanding the national character of the people. They are understandable and accessible to different nations, as they are based on typical life situations, reflect the logical thinking of the people.